2004
DOI: 10.1002/bjs.4756
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of helicopter emergency medical services on survival of severely injured patients

Abstract: The presence of the HMT may increase chances of survival for patients suffering multiple trauma, especially for those with blunt trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 26 publications
1
71
0
1
Order By: Relevance
“…Frankema et al 26 found that after adjustment for injury severity, time of day, and other physiological variables, transportation of a highly trained medical crew to the scene was associated with a nonstatistically significant difference in survival (OR, 2.2; 95% CI, 0.92-5.9; P =.08). Blunt trauma patients transported by helicopter in the study by Frankema et al had a statistically significant survival improvement (OR, 2.8; 95% CI, 1.07-7.52; P=.04).…”
Section: Commentmentioning
confidence: 99%
“…Frankema et al 26 found that after adjustment for injury severity, time of day, and other physiological variables, transportation of a highly trained medical crew to the scene was associated with a nonstatistically significant difference in survival (OR, 2.2; 95% CI, 0.92-5.9; P =.08). Blunt trauma patients transported by helicopter in the study by Frankema et al had a statistically significant survival improvement (OR, 2.8; 95% CI, 1.07-7.52; P=.04).…”
Section: Commentmentioning
confidence: 99%
“…The reason for this is that there has never been designed a prospective randomized study to assess the usefulness of physician-staffed prehospital trauma teams. Though, several retrospective studies indicated that the MMT in the Netherlands offers an increased chance of survival for severely injured patients and could lead to reduced morbidity [8][9][10]. In studies conducted among prehospital traumatic deaths, airway management has been shown the key in preventable deaths in patients with severe head injury [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate triage and bypass protocols (whereby patients with major trauma are taken directly to a major trauma centre, potentially bypassing closer EDs) are therefore essential [3,46,67,68]. Helicopter transfer to definitive care has recently been demonstrated to reduce mortality from major trauma [69], but this is in addition to evidence that physicians bring survival benefits to the pre-hospital phase of trauma care [70,71].…”
Section: Pre-hospital Carementioning
confidence: 99%